An Economic Life in Vain - Path Dependence and East Germany's Pre- and Post-Unification Economic Stagnation - Ulrich Blum (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2011)
20 years after unification, the East German twin's economic position is relatively stagnant compared to most of the West German productivity and income variables. The strong initial takeoff until the mid-end 1990s ended at a level of 70% to 80% of the western reference. In this paper, two interdependent hypotheses are put to the test: (i) that the communist economy prior to unification was on a stagnating path contrary to what standard analyses show; (ii) that strong elements of path dependence exist and that the switch from plan to market offset the pre-unification stagnation but was not able to repair structural deficits inherited from the past. In fact, looking into West German long-term data, an extremely stable development path can be found that extends from the 19th century to the present. Thus, the analysis of the East German development path is both economically relevant and politically interesting if economic policies are to be formulated ... – – 20 Jahre nach dem Vollzug der Einheit stagniert die Wirtschaftsentwicklung des 'ostdeutschen Zwillings' im Vergleich zu westdeutschen Einkommens- und Produktionskennzahlen. Der starke Wachstumsschub bis in die Mitte der 1990er Jahre ebbte ab, und die Wirtschaft verharrt seitdem auf einem Niveau, das 70% bis 80% der westdeutschen Referenzgrößen entspricht. In diesem Beitrag werden zwei voneinander unabhängige Hypothesen überprüft: (i), dass bereits die kommunistische Wirtschaft Ostdeutschlands vor der Einheit auf einem Stagnationspfad war, ganz im Gegensatz zu dem, was andere Untersuchungen ausweisen; (ii), dass eine starke Pfadabhängigkeit existiert und der Umstieg von der Zentralverwaltungs- zur Marktwirtschaft nur diese vorangegangene Stagnationsphase kompensierte, die tiefer liegenden strukturellen Defizite aber nicht löste. Im Falle Westdeutschlands reicht ein stabiler Entwicklungspfad vom 19. Jahrhundert in die Gegenwart. Daher ist die Analyse des ostdeutschen Entwicklungspfads gleichzeitig ökonomisch relevant und wirtschaftspolitisch bedeutsam ...
urn:nbn:de:101:1-201108193498
Keywords: N0; O1; P2; 330; East Germany; time series; income; institution; product; unification; economic growth; convergence; Ostdeutschland; Einkommen; Institution; Einheit; Wachstum; Konvergenz